Development and Characterization of High Power Density IGBT Module - LIU Guo-you; QIN Rong-zhen; HUANG Jian-wei; Ian Deviny; LUO Hai-hui; Rupert Stevens; WU Yi-bo (机车电传动)
Based on the standard DMOS technologies, the IGBT&FRD chip set and module structures were improved to realize lower